PENGARUH SISTEM E-SIMPEL “SISTEM INFORMASI PELAYANAN ONLINE” DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL (DISPENDUKCAPIL) KABUPATEN GROBOGAN TERHADAP PELAYANAN PUBLIK TAHUN 2025 - Ivana Aruliya Risaldi; Neny Marlina (Journal of Politic and Government Studies, 2026)
The development of information technology encourages the government to innovate in the delivery of public services through the implementation of digital-based systems, one of which is the E-SIMPEL System (Online Service Information System) implemented by the Grobogan Regency Population and Civil Registration Service to improve the quality of population administration services. This system is designed to provide easier access to services for the community more effectively and efficiently, but in its implementation there are still obstacles such as limited digital literacy in the community and the readiness of technological infrastructure. Therefore, this research formulates the problem regarding the influence of implementing the E-SIMPEL System in improving public services and aims to analyze its influence on the quality of public services using the theoretical basis of e-government and the concept of service quality which includes the dimensions of reliability, responsiveness, assurance, empathy and tangible through a descriptive quantitative approach with a survey method of 90 respondents using a Likert scale which is analyzed using validity, reliability and simple linear regression tests with the help of SPSS. The research results show that the implementation of the E-SIMPEL System has a positive and significant effect on the quality of public services with a calculated t value of 14.101 which is greater than the t table of 1.987 and a significance level of 0.000 < 0.05, as well as a correlation coefficient value of 0.833 which shows a strong relationship and a coefficient of determination (R²) of 0.693 which shows a contribution of 69.3%. Based on these results, it is concluded that the E-SIMPEL system has a significant influence in improving the quality of public services at the Grobogan Regency Population and Civil Registration Service, increasing the effectiveness and efficiency of services and facilitating public access, so it is recommended that local governments continue to develop the system, increase outreach, and strengthen technological infrastructure to support the optimization of digital-based public services.